A STUDY ON THE QUALITY OF VARIOUS TYPES OF CHEESE PRODUCED AND CONSUMED IN GREECE - ΣΚΟΥΝΤΖΟΣ, Κ.; ΑΣΙΚΗΣ, Ι. (Journal of the Hellenic Veterinary Medical Society, 1974)
Laboratory examination of 828 samples of four typss of Greek cheese («telemes» : 415, «kasseri» : 164, «kefalotyrion» : 170, «gruyère» : 79) obtained from the Attikan market area, revealed, that : a. There is great variation relative to the water as well as the fat contents of the various types of cheese, resulting in the lack of standardized organoleptic and quantitative characteristics in the types of cheeses sold. b. The «kefalotyrion» cheese in particular contains significantly high quantities of sodium chloride. The authors suggest that ins criterion of fat content established so far for the quantitative classification of Greek cheese types be replaced by the criterion of protein content.